Advertising that sells: a primer for product managers - Raymond, Miner (New York: Black Rose, 1989)
How and Why This Book Go Written - Executing the Strategy - The Brand Differentiating Message - The Storyboard - Scene Objectives - The Heavy Cost of Rush Production - The Preproduction Meeting - A Client Bill Of Rights
Incluye index
Keywords: Marketing; Publicidad